Pengembangan Sistem Informasi Customer - Touching Applications Unit Simpan Pinjam Menggunakan Metode RUP (Studi Pada KPRI "GURU" Kecamatan Sumbermanjing Wetan) - Fatih Ulil Albab; Yusi Tyroni Mursityo; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
KPRI "GURU" Kec.. Sumbermanjing Wetan is a corporation consisting of civil servant teachers in Sumbermanjing Wetan. One part of this corporation is a unit simpan pinjam, a service of savings and loans for its members. The currently savings and loan unit business process is still manually, where all activities can only be done at KPRI office. This raises the problem, because the natural condition of Sumbermanjing Wetan is vast and hilly area, it's allows KPRI members to move to more accessible corporation. Therefore an information system based on Customer Relationship Management (CRM) strategy especially Service Automation is needed to maintain the loyalty of corporation members. Result from this study is a Customer - Touching Applications to ease members in the savings and loan activity. In the developing system RUP method used because it can accommodate changes during development when developed the system included in the financial system which the functionality is a great concerned. The developed system has 23 functional requirements to support business processes on savings and credit units. Testing on system were performed by black box test there are 67 test case to test functional requirement system with 100% result and compatibility to test non functional requirement with result of 2 critical issue. UAT testing is used to determine whether the system is accepted by the end user and generates an acceptance value of 83.123%